1980
DOI: 10.1203/00006450-198001000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Effects of Acute Meconium Obstruction on Pulmonary Function

Abstract: The relationship between pulmonary function and the migration of meconium to distal airways was determined in 10 rabbits (mean weight 2.6 kg) after insufflation of a meconium-saline mixture (1--2 ml/kg). Animals were anesthetized, cannulated, intubated, and mechanically ventilated with 100% oxygen. Lung mechanical dysfunction was most severe during the early phase of meconium migration, 15 min postinsufflation. Substantial increases in inspiratory lung resistance (RI) and expiratory lung resistance (RE) sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(24 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…Initial deterioration in neonatal lung mechanics after aspiration of meconium is supposed to be mainly obstructive, caused by thick or particulate meconium blocking the airways partially or completely (3,6). Experimental investigations have shown that dynamic lung compliance drops rapidly during the first hour after meconium insufflation and remains low for the first days after the insult (3,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial deterioration in neonatal lung mechanics after aspiration of meconium is supposed to be mainly obstructive, caused by thick or particulate meconium blocking the airways partially or completely (3,6). Experimental investigations have shown that dynamic lung compliance drops rapidly during the first hour after meconium insufflation and remains low for the first days after the insult (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal aspiration of meconium frequently produces respiratory failure with hypoxemia, hypercapnia, and acidosis in the newborn infant and may be complicated by air leaks, pulmonary hypertension, hypoxic organ damage, and long-term pulmonary sequelae (1,2). The pathophysiology of the meconium aspiration syndrome (MAS) is complex and includes initial mechanical obstruction of the airways, ventilation/perfusion mismatch, surfactant inactivation, and progressively developing inflammatory lung injury (1)(2)(3)(4)(5)(6). Aspirated meconium may directly damage the alveolar-capillary membrane and may also augment pulmonary injury through activation of alveolar macrophages, inflammatory cytokine production, and accumulation of polymorphonuclear neutrophils (PMNs) (1,2,6,7).…”
mentioning
confidence: 99%
“…In a similar model, it has been shown that mechanical dysfunction in lungs is most severe during the early phase of MAS, with diminished dynamic and specific lung compliance, but unchanged static lung compliance, suggestive of partial random obstruction of large airways. 32 This study, however, is limited in its duration, and effects occurring more than 2 hours following meconium aspiration were not evaluated. Similar findings were observed by Yeh and colleagues 33 who evaluated pulmonary function tests in the first 3 days of life in neonates with mild MAS not requiring mechanical ventilation.…”
Section: Pathophysiology Of Meconium Passagementioning
confidence: 99%
“…It is supposed that in the early stages presence of the amniotic fluid can be associated with an increase of pulmonary resistance, dysfunction of surfactant, decrease of dynamic compliance of the lungs, hypoxemia with hypercapnia [14,15].…”
Section: Introductionmentioning
confidence: 99%